DEPICTION OF SOCIAL DISPARITY IN HAROLD PINTER’S THE BIRTHDAY PARTY: MARXIST CRITICISM - ILHAM DARMAWAN (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
This study analyzes Harold Pinter’s play The Birthday Party using Marxist literary criticism, especially Karl Marx and Friedrich Engels’ idea of class struggle from The Communist Manifesto (1848) and Georg Lukács’s perspective of reflectionism. The purpose of this research is to show how the play represents social disparity through its characters and conflicts. Stanley is portrayed as a powerless and marginalized individual, similar to the proletariat, while Goldberg and McCann represent authority and domination, similar to the bourgeoisie. Their use of language, intimidation, and control shows how power works in society. By combining Marx’s class conflict with Lukács’s view of literature as a mirror of society, this study connects the play with the social condition of post-war Britain, where people often felt alienated and insecure. The result of the analysis shows that The Birthday Party is not only an absurd drama but also a reflection of real social inequality and the struggles between different classes.